The Effect of Event Prestige on Event Participation Intention: The Case of the FISU World University Summer Games - Daogang He; Xi Chen (Urban Science, 2022)
Mega sports events play an important role in the development of the host city. This study examined the relationship between event prestige, city image, place attachment, and event involvement intention of the host community. Data were obtained using questionnaires distributed to college students in Chengdu, China 2022, when it was the host of the World University Games. The results show that the event’s prestige as perceived by college students had a significant positive impact on the intention to participate in the event, and the event’s prestige had a significant positive impact on the image of the city but had no effect on the place attachment of college students. City image and place attachment has a chain mediating effect between the event prestige and the participation intention. Moreover, hosting an event can form a positive image of the host city, thus further enhancing the place attachment of college students, and providing talent protection for urban development. The implications of these findings for the event’s organization strategies as well as future research directions are discussed.